Long term quality of life after laparoscopic antireflux surgery for the elderly - Tolone, Salvatore (BioMed Central, 2013)
BACKGROUND: Studies have previously shown laparoscopic antireflux surgery is a safe and effective treatment for GERD even in elderly patients. The aim of the current study was to evaluate patients receiving laparoscopic antireflux surgery before and after 65 years of age and to assess their surgical outcomes and improvements in long term quality of life. METHODS: Patients were given a standardized symptoms questionnaire and the Short-Form 36 Health Survey for quality-of-life evaluation before and after laparoscopic total fundoplication. RESULTS: Forty-nine patients older than 65 years of age were defined as the elderly group (EG) whereas the remaining 262 younger than 65 years of age were defined as the young group (YG). There were 114 (36.6%) patients who filled out the SF36 questionnaire (98 in the younger group, rate: 37.4%; 16 in the elderly group, rate: 32.6%) pre- and post-operatively. There was no significant difference between the two age groups regarding preoperative PCS ( 45.6 ± 7.8 in YG vs. 44.2 ± 8.2 in EG; P = 0.51) and MCS ( 48.1 ± 10.7 in YG vs. 46.9 ± 9.2 in EG; P = 0.67). There was no significant difference between the two age groups regarding postoperative PCS (49.8 ± 11.9 in YG and 48.2 ± 9.5 in EG ; P = 0.61 and MCS (48.4 ± 10.7 in YG vs. 50.1 ± 6.9 in EG; P = 0.54). CONCLUSIONS: In conclusion, laparoscopic total fundoplication is a safe and effective surgical treatment for gastroesophageal reflux disease generally warranting low morbidity and mortality rates and a significant improvement of symptoms comparable. An improved long-term quality of life is warranted even in the elderly.